Предмет: Алгебра, автор: pdmpyavqktsb

(2a^2-3a+1)-(7a^2-5a)

Ответы

Автор ответа: rudemak
0

Ответ:

Объяснение:

(2a^2-3a+1)-(7a^2-5a)=2a^2-3a+1-7a^2+5a=-5a^2+2a+1

Автор ответа: maxum000
0

Ответ:

(2a^{2}-3a+1) -(7a^{2}-5a) =  2a^{2}-3a+1-7a^{2} +5a = -5a^{2} +2a+1  \\\\5a^{2} -2a-1 = 0\\D =  (-2)^{2} -4*5*(-1) = 4+20=24\\\\a_{1} = \frac{-(-2)+2\sqrt{6} }{2*5} = \frac{2(1+\sqrt{6})  }{2*5} =  \frac{1}{5} + \frac{1}{5}  \sqrt{6} \\a_{2} = \frac{-(-2)-2\sqrt{6} }{2*5} = \frac{2(1-\sqrt{6})  }{2*5} =  \frac{1}{5} - \frac{1}{5}  \sqrt{6}

Похожие вопросы
Предмет: Қазақ тiлi, автор: nuspechkov4